The Ten Cs Of Chronic Care - Sanjay Kalra; Madhur Verma; Nitin Kapoor (Journal of the Pakistan Medical Association, 2024)
Much has been written, and much more has been said, about the unique challenges and demands of chronic disease management. Various chronic disease models, including Chronic Care Model (CCM), Improving Chronic Illness Care (ICIC), and Innovative Care for Chronic Conditions (ICCC), Stanford Model (SM) and Community based Transition Model (CBTM), have been studied1. Most physicians are trained in acute care, and attend to disease (and health) in a cross-sectional manner. Chronic disease care, however requires a long term, or longitudinal approach to management. While various experts have discussed the differences between acute or chronic disease care, it becomes challenging for younger doctors to understand these intricacies. Continuned...